Pengaruh Kemudahan Penggunaan Terhadap Keputusan Pembelian Online Food Delivery ShopeeFood - Djakaria, Azka Zarkasya (International Journal Administration, Business & Organization, 2023)
The purpose of this study is to determine the effect of ease of use on purchasing decisions for online food delivery through ShopeeFood for students majoring in Commercial Administration, Bandung State Polytechnic. This research uses a quantitative descriptive method. Data collection was carried out by distributing questionnaires through the Google Form. Respondents totaled 100 people who had made purchases using ShopeeFood. The analytical method used is simple linear regression analysis. The results show that ease of use has a positive effect on purchasing decisions by 54.8%.